2014
DOI: 10.1124/jpet.114.218263
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Receptors Trigger cAMP Production and Inhibit Chloride Movements in Nonpigmented Ciliary Epithelial Cells

Abstract: Melatonin and its analog 5-MCA-NAT (5-methylcarboxyamino-N-acetyl tryptamine) are active compounds reducing intraocular pressure (IOP). This action is mediated through MT 2 and the putative MT 3 melatonin receptor, producing a transient reduction of IOP that lasts for a few hours and has not yet been characterized. The use of melatonin and its analog are causing a decrease in chloride efflux from rabbit nonpigmented epithelial cells (NPE), possibly explaining the decrease in IOP. Melatonin and 5-MCA-NAT inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 52 publications
3
36
3
1
Order By: Relevance
“…This melatonin, acting in an autocrine way through melatonin receptors present in the ciliary processes (Alarma-Estrany et al, 2009, 2011, could reduce chloride production from the ciliary epithelium as recently described (Huete-Toral et al, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…This melatonin, acting in an autocrine way through melatonin receptors present in the ciliary processes (Alarma-Estrany et al, 2009, 2011, could reduce chloride production from the ciliary epithelium as recently described (Huete-Toral et al, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…Three concentrations (10 -9 M, 10 -7 M, and 10 -3 M) of the hormone were employed for the study because previous in vitro experiments have PRACE ORYGINALNE (10 -3 M ) concentration melatonin had the opposite effect on the studied process [8][9][10][11][12]. On the other hand, the concentrations of both antagonists (10 -6 M and 10 -5 M) were chosen for our present experiments because they were demonstrated to be the most effective in action [24][25][28][29][30][31]. Several studies have shown that luzindole antagonises the effects of melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…The first two are negatively coupled to adenylate cyclase, whereas MT 3 seems to be positively linked to the same signal transduction mechanism (Huete-Toral et al, 2015). There is controversy regarding these receptors, since some authors claim that MT 3 receptors are quinone reductase 2 (Nosjean et al, 2000), but this identity has not been demonstrated in ocular tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Since the mentioned adrenoceptor may contribute to the regulation of IOP as previously described (Pintor, 2009), it is possible that the application of prazosin may reflect an action on a1 adrenergic receptors rather than MT 3 melatonin receptors. To clarify this point, we recently described that when prazosin is topically applied at micromolar concentrations, the intraocular concentration of this antagonist acts mainly on the MT 3 melatonin receptor rather than on the a1 adrenergic receptor, thus discarding the possible interaction with the adrenergic receptor (Huete-Toral et al, 2015).…”
mentioning
confidence: 99%